2008
DOI: 10.1007/s00508-008-1084-4
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral face swelling as first manifestation of metastatic pancreatic cancer: Case report and review of the literature

Abstract: In making the decision on whether metastasectomy should be performed in an uncommon site of metastatic spread such as the mandibula, both the possibility of cure and also the potentially decreased response to conservative therapy and the patient's decreased quality of life have to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…and Vormittag et al . showed that metastases of malignant tumor should also be considered on differential diagnosis ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…and Vormittag et al . showed that metastases of malignant tumor should also be considered on differential diagnosis ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%